Predicting the Role of Admission Blood Pressure Parameters for Short-Term Clinical Outcome in Community-Acquired Pneumonia at a Tertiary Care Hospital In Bangladesh - Hossain, Md Monoar; Islam, Md Khairul; Haque, Nazmul; Rashid, Md Mamunur; Zaman, Mohammad Monir Uz (Bangladesh Journal of Medicine, 2025)
Background: Community-acquired pneumonia (CAP) remains a life-threatening condition, especially in developing countries. On admission, blood pressure parameters can be crucial in assessing disease severity. The aim of the study was to identify hemodynamic predictors of for short-term Clinical Outcome in patients in CAP. Methods: This prospective observational study was conducted in the Department of Medicine at Dhaka Medical College Hospital from September 2022 to August 2023 and included 150 patients diagnosed with CAP. Blood pressure measurements were taken within four hours of admission. All patients received standard treatment as per hospital protocol. The attending physician decided to initiate inotropic support and need for mechanical ventilation. The primary outcomes assessed were 30-day mortality and the requirement for inotropic support or mechanical ventilation. Follow-up assessments were conducted on days 3 and 7 or at discharge, whichever occurred earlier. An additional follow-up was performed via telephone on day 30. Data were recorded on a structured data collection sheet. Multivariate logistic regression was performed to identify independent predictors. Moreover, receiver operating characteristic (ROC) curve analysis was conducted to evaluate predictive performance. Results: Fourteen percent of 150 patients died on admission and 23.3% needed ventilation/inotropes. At 30 days, mortality was 22.6% and 34.7% needed ventilation/ inotropes. sBP<90 mmHg, dBP d”60 mmHg, pulse pressure £40 mmHg, and MAP <70 mmHg were significant for both outcomes (p<0.001). On multivariate analysis, systolic BP <90 mm Hg (OR 5.439; CI 1.565–18.895) and MAP <70 mm Hg (OR 4.465; CI 1.280–15.579) were found to be predictors of 30-day mortality. These also were predictive of the need for ventilation/inotrope (ORs 2.958 and 2.807). ROC analysis showed very good predictive power of systolic BP (AUC 0.852–0.922) and MAP (0.835–0.914), good-to-moderate of diastolic BP and pulse pressure. Conclusion: Upon admission, systolic blood pressure and MAP are strong predictors of short-term mortality and requirement of advanced support in CAP patients. Bangladesh J Medicine 2025; 36(3): 101-108